Broadband emission in all-inorganic metal halide perovskites with intrinsic vacancies. Issue 40 (13th October 2020) - Jiang, Feng; Jiang, Xingxing; Zheng, Weihao; Ouyang, Yu; Zhang, Yushuang; Li, Lihui; Fan, Peng; Zhao, Hepeng; Li, Yang; Jiang, Ying; Zhu, Xiaoli; Zhuang, Xiujuan; et al.
Abstract : Introducing some lanthanide ions with suitable ionic radius into octahedral [PbX6 ] units to cause permanent lattice distortion and create potential fluctuations in the crystal lattice might facilitate the formation of STEs in CsPbX3 . Abstract : Efficient broadband emission related to self-trapped excitons (STEs) in low-dimensional perovskites and double perovskite crystals has attracted great attention due to its potential applications in optoelectronics. However, the formation of STEs in three-dimensional (3D) all-inorganic perovskites (CsPbX3 ) is difficult. Here, through the doping of ytterbium (Yb 3+ ) or erbium (Er 3+ ) ions into CsPbX3 crystals, we observed broadband luminescence from STEs with a linewidth exceeding 200 nm and a Stokes shift of ∼1 eV. Theoretical concepts and experimental studies demonstrated that Pb 2+ in perovskites could be replaced by impure ions. Also, the Pb 2+ substitution defects and adjacent halide vacancies introduced defect states lying just below the conduction band minimum of perovskites. Strong electron–phonon coupling between trapped carriers and deformation of the [PbX6 ] cage reduced the energy gap of perovskites. Our study sheds new light on the permanent defects induced in extrinsic STEs in 3D inorganic perovskites. It also provides a clear microscopic picture of the underlying mechanism of formation of STEs.